High Gain Compact Strip and Slot UWB Sinuous Antennas - Elson Agastra; Leonardo Lucci; Giuseppe Pelosi; Stefano Selleri (International Journal of Antennas and Propagation)
Three ground-backed compact strip-and slot-sinuous antennas are analyzed. Proposed configuration allows for a single lobe, polarization-versatile, high efficiency, and ultrawide band antenna not needing a cumbersome lossy back cavity typical of conventional single-lobe sinuous antennas. Simulations show attained performances as well as tuning possibilities.